Chronic stress experience and burnout syndrome have appreciable influence on health‐related quality of life in patients with psoriasis. (2nd March 2015) - Breuer, K.; Göldner, F.M.; Jäger, B.; Werfel, T.; Schmid‐Ott, G.
Abstract Background Psoriasis has a negative impact on health‐related quality of life (HRQoL) and may favour mental comorbidity. Objective To investigate the contribution of chronic stress and burnout experience to HRQoL and how mental health influences the efficacy of an inpatient rehabilitation measure in psoriasis patients. Methods Eighty‐four psoriasis patients taking part in a 3‐week inpatient rehabilitation measure participated in the study. Severity of psoriasis was assessed with the Psoriasis Area and Severity Index (PASI) and by patients' self‐evaluation at the beginning and end of treatment. The following aspects of mental health were explored using validated questionnaires. Symptoms of chronic stress and burnout experience: Trier Inventory for the Assessment of Chronic Stress (TICS) and Shirom Melamed Burnout Measure (SMBM). Symptoms of depression: depression scale of the Patient Health Questionnaire in the German version (PHQ‐D). HRQoL: Dermatology Life Quality Index (DLQI) and Short Form Health Survey‐8 (SF‐8). Results Linear regression analyses revealed that chronic stress, burnout experience and perceived symptom severity but not clinician‐assessed severity of psoriasis had independent negative effects on HRQoL. Patients who achieved a PASI reduction of <75% at discharge from the rehabilitation measure had lower baseline QoL and showed more symptoms of depression, chronic stress and burnout than patients who achieved a PASI improvement of ≥75. Conclusion Chronic stress and burnout have appreciable influence on HRQoL and may adversely affect treatment success in psoriasis patients. Our data underscore the importance of a multidimensional approach in the management of psoriasis.